COMPARISON OF BACTERIAL PROBIOTICS (BIFIDOBACTERIUM AND LACTOBACILLUS) VERSUS FUNGAL PROBIOTICS (SACCHAROMYCES) IN TREATING ACUTE DIARRHEA IN CHILDREN AGED 6 MONTHS TO 5 YEARS - Safar Ali Shah; Samia Naz; Fazaila Jabeen; Rashid, Muhammad Adnan; Abdul Rahman; Zeeshan Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute diarrhoea among children mainly due to infection must be treated prophylactically to reduce mortality. The objective of this study was to compare the outcome of using bacterial probiotics (Bifidobacterium and Lactobacillus) versus fungal probiotics (Saccharomyces) for acute diarrhoea among children aged 6 months to 5 years. Methods: A non-randomized control trial was conducted at diarrhoea ward, the Children’s Hospital, Lahore from 1st March 2022 to 1st March 2024. 200 children were recruited in the study using non-probability consecutive sampling technique which were divided equally into two groups receiving either bacterial probiotics or fungal probiotics. The children were followed up till resolution of diarrhoea. Diarrhoeal duration and stool frequency were noted. Data was entered and analysed using SPSS Version 26. Results: Out of 200 children, 52.5% were male and 47.5% were female. Mean age of the sample was 2.24±1.54 years, mean baseline and follow up diarrhoea duration was 3.52±1.44 and 3.47±1.25 days and stool frequency at follow up was 3.75±1.15. Complete diarrhoeal resolution was seen among 95% of the children using bacterial probiotics while 87% of the children using fungal probiotics (p=0.048). Regarding diarrhoeal duration (days) among the two groups, the mean was 3.11±1.36 (bacterial probiotic group) and 3.88±1.02 (fungal probiotic group) (p<0.001) and regarding stool frequency, the mean was 2.97±0.55 (bacterial probiotic group) and 4.57±1.07 (fungal probiotic group) (p<0.001). Conclusion: It can be concluded from this study that diarrhoeal resolution along with stool frequency was better among children using bacterial probiotics as compared to those using fungal probiotics.